The Toronto Empathy Questionnaire: Reliability and Validity in a Nationwide Sample of Greek Teachers - Ntina Kourmousi (Social Sciences, 2017)
The present study examined the Toronto Empathy Questionnaire’s (TEQ) validity and reliability in a sample of 3955 Greek teachers. In order to test the internal consistency reliability, the Cronbach’s alpha coefficient was used and was found satisfactory at 0.72. The sample was randomly split and an exploratory factor analysis (EFA) was conducted in the even subsample, justifying the one-factor solution, with the only discrepancy of the low loading of an item. In the odd subsample a confirmatory factor analysis (CFA) was performed to confirm the one-factor model identified by the EFA. The chi square test (χ2) of the model was significant (p < 0.05), while the root mean square error of approximation (RMSEA), the comparative fit index (CFI) and the goodness of fit index (GFI) values were 0.078, 0.969 and 0.960, respectively, further supporting the model’s fit. Student’s t-tests and analysis of variance (ANOVA) showed that women, teachers with children of their own, those working full-time in public schools, those with students who needed special education, and those who had received mental health promotion training, scored higher. Additionally, multiple linear regression analysis revealed that sex, working status, having students who needed special education, and having attended mental health training courses were independently associated with TEQ score. The analyses confirmed that the Greek version of TEQ could be used for researches in Greek educators as a valid and reliable measure of teachers’ empathy.